Evaluating the Use of Marlin Fish (Istiompax indica) By-product Meal in the Ration on Carcass and Organ Yields of Broiler Chickens - Zulfan, Zulfan Zulfan; Daud, Muhammad; Latif, Herawati; Khairunnisa, Novia; Anggraini, Tantri (Buletin Peternakan, 2024)
This study aimed to examine the effect of marlin fish (Istiompax indica) byproduct meal (MFBM) mixed with some other feed ingredients such as yellow corn (YC), rice bran (RB), broken rice (BR), and top mix (TM) as a mixture feed (MF) in replacement fractionally a commercial ration (CR) on carcasses and organs of broiler chickens. As a comparison,  commercial local fish meal (CLFM) was used instead of MFBM in the MF. A total of 100 DOCs, strain MB 202, were raised for 35 days of age to feed the experimental rations. The experimental rations were: CR= 100% CP511/512 (control), MFBM4= 80% CP511/512 + 20% MF1 containing 4% MFBM, MFBM8= 80% CP511/512 + 20% MF2 containing 8% MFBM, CLFM4= 80% CP511/512 + 20% MF3 containing 4% CLFM, and CLFM8= 80% CP511/512 + 20% MF4 containing 8% CLFM. The research used a completely randomized design (CRD) with five treatments, four replications, and two subsamples. Data were analyzed by Analysis of Variance (ANOVA) and continued by Duncan’s multiple range taste (DMRT) only if the results detected a significant difference. This study showed that at 4% usage within the MF, using MFBM did not indicate a significant difference in the whole carcass and cuts-up weights than using CLFM. However, at the level of 8% within an MF, the former was significantly higher (p<0.05) on the whole carcass and breast weight than the latter. In conclusion, marlin fish byproduct meal (MFBM) could be used up to 8% to produce better whole carcass and breast weight compared to commercial local fish meal (CLFM) without adverse effects on the internal organs of broilers.